PCSK9 Modulates the Secretion But Not the Cellular Uptake of Lipoprotein(a) Ex Vivo - Elise F. Villard, PhD; Aurélie Thedrez, PhD; Jorg Blankenstein, PhD; Mikaël Croyal, BSc; Thi-Thu-Trang Tran, PhD; Bruno Poirier, PhD; Jean-Christophe Le Bail, PhD; Stéphane Illiano, PhD; Estelle Nobécourt, MD, PhD; Michel Krempf, MD, PhD; Dirk J. Blom, MD, PhD; A. David Marais, MD; et al. (JACC: Basic to Translational Science, 2016)
To elucidate how the proprotein convertase subtilisin kexin type 9 (PCSK9) inhibitor alirocumab modulates lipoprotein(a) [Lp(a)] plasma levels, the authors performed a series of Lp(a) uptake studies in primary human hepatocytes and dermal fibroblasts and measured Lp(a) secretion from human hepatocytes. They found that Lp(a) cellular uptake occurred in a low-density lipoprotein receptor–independent manner. Neither PCSK9 nor alirocumab altered Lp(a) internalization. By contrast, the secretion of apolipoprotein (a) from human hepatocytes was sharply increased by PCSK9, an effect that was reversed by alirocumab. They propose that PCSK9 does not significantly modulate Lp(a) catabolism, but rather enhances the secretion of Lp(a) from liver cells.